Linking vascular disorders and Alzheimer’s disease: Potential involvement of BACE1 - Cole, Sarah L. (2008)
The etiology of Alzheimer’s disease (AD) remains unknown. However, specific risk factors have been identified, and aging is the strongest AD risk factor. The majority of cardiovascular events occur in older people and a close relationship between vascular disorders and AD exists. Amyloid plaques, composed of the beta amyloid peptide (Aβ), are hallmark lesions in AD and evidence indicates that Aβ plays a central role in AD pathophysiology. The BACE1 enzyme is essential for Aβ generation, and BACE1 levels are elevated in AD brain. The cause(s) of this BACE1 elevation remains undetermined. Here we review the potential contribution of vascular disease to AD pathogenesis. We examine the putative vasoactive properties of Aβ and how the cellular changes associated with vascular disease may elevate BACE1 levels. Despite increasing evidence, the exact role(s) vascular disorders play in AD remains to be determined. However, given that vascular diseases can be addressed by lifestyle and pharmacologic interventions, the potential benefits of these therapies in delaying the clinical appearance and progression of AD may warrant investigation.